PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL UNTUK SISWA KELAS X SMAN 2 LENGAYANG - Mita Purnama Sari (Jurnal Edukasi dan Penelitian Matematika, 2021)
This study aims to develop learning tools with PMRI approach on SPLTV material for class X SMA/MA. The learning tools developed were assessed based on their validity and practicality. This type of research is development research with the Plomp development model, namely the initial investigation, development or prototyping stage  and  the  assessment  stage.  At   the   initial  investigation  stage,  needs  analysis, curriculum analysis, concept analysis, and student analysis were carried out in order to obtain  the  characteristics  of  the  form  of  learning  tools  developed.  At  the development/prototyping  stage,  a  prototype  learning  device  design  in  the  form  of  RPP and LKPD is made using the PMRI approach for SPLTV material. The prototype used will go through formative evaluation such as self-evaluation and evaluation with experts to  get  a  valid  prototype.  Furthermore,  at  the  last  stage  is  the  assessment  stage,  at  this stage the goal is to get the practical criteria for the LKPD prototype after conducting an individual evaluation. In this study, it was carried out when the pandemic was endemic, so  in  this  study  there  were  several  stages  that  could  not  be  carried  out  properly.  This research was only carried out until the stage of development/prototyping of the one-on- one  evaluation  section.  The  conclusion  of  this  research  is  that  learning  tools  using  the PMRI approach on SPLTV materials, namely RPP and LKPD, can be said to be valid and practical. Keywords − learning tools, SPLTV, PMRI